Pemeriksaan Kesehatan Gratis (Pemeriksaan Tekanan Darah, Kadar Gula Darah, Dan Asam Urat) Di GBKP Tiga Panah - Daniel Ginting; Nina Fentiana (FKIP, Universitas Palangka Raya, 2023)
Early detection of non-communicable diseases (PTM) such as hypertension, diabetes mellitus and joints is needed as a preventive measure. The government through Government Regulation Number 2 of 2018, Minister of Home Affairs Regulation Number 100 of 2018, and Minister of Health Regulation Number 4 of 2019 has determined that efforts to control diabetes mellitus are one of the minimum services that must be carried out by regional governments. Activities carried out are health checks which include checking blood pressure, checking blood sugar, and uric acid. The activity was attended by the community in the Tiga Panah GBKP environment. Examination results showed that there were 38.5% of the population with normal blood pressure. 53.8% of the population with normal blood sugar levels and 38.5% of the population with normal uric acid levels. This health examination is the first step for early detection of non-communicable diseases (PTM) so that later it can be continued for routine checks at local health service facilities.